(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article described aspect the south folklore which gives description from the mankind. And in this article said that about parallels animals and mankind. As we know Nasreddin Afandi was a joke man, Silliman, clear thinkable, person with sharp or quick wits, jokeless and of course was honest and respectable person.